Lifelong Learning Policies for Young Adults in Europe Navigating between Knowledge and Economy - Parreira do Amaral, Marcelo; Kovacheva, Siyka; Rambla, Xavier (Policy Press, 2019)
"Available Open Access under CC-BY-NC licence. This comprehensive collection discusses topical issues essential to both scholarship and policy making in the realm of lifelong learning (LLL) policies and how far they succeed in supporting young people across their life courses, rather than one-sidedly fostering human capital for the economy. Examining specific yet diverse regional and local contexts across Europe, this book uses original research to evaluate differences in scope, approach, orientation, and objectives. It examines the embedding of LLL policies into the regional economy, the labour market, education and training systems and the individual life projects of young people, with a focus on those in situations of near social exclusion. "